PtSe2 phototransistors with negative photoconductivity. Issue 1 (April 2021) - Di Bartolomeo, A; Urban, F; Faella, E; Grillo, A; Pelella, A; Giubileo, F; Askari, M B; McEvoy, N; Gity, F; Hurley, P K
Abstract: Platinum diselenide (PtSe2 ) is one of the most studied materials of the emerging group-10 transition-metal dichalcogenides. We investigate the electrical conduction and the photoconduction of PtSe2 ultrathin films exploited as the channel of back-gated field-effect transistors. The channel resistance decreases with the rising temperature and shows that the films have semiconducting behaviour. The gate modulation confirms a p-type conductivity with field-effect mobility up to 30 cm 2 /(Vs). Under exposure to the radiation from a super-continuous white light source, a reduction of the PtSe2 electrical conductivity (negative photoconductivity) is observed in low vacuum, while a positive photoconductivity emerges only under high-power illumination conditions. Although, the positive photoconductivity arises from conventional photoconductive effect, the negative photoconductivity can be explained as the combination of the photogating effect caused by charge accumulation in the SiO2 dielectric and the photo-induced desorption of adsorbates.